Conformational changes of PsbQ protein from PSII studied by NMR - Primasová, Hedvika (Jihočeská univerzita, 2016)
PsbQ is an extrinsic protein of photosystem II (PS II) playing a role in calcium and sodium homeostasis for oxygen evolving complex in photosynthesis. The solution structure of PsbQ in phosphate buffer including a short N-terminal helix has been resolved recently. The incorporation of PsbQ in PS II and its interactions with other PS II proteins were not elucidated yet. As a prerequisite for detailed interaction studies with other extrinsic PS II proteins such as PsbP, suitable conditions for nuclear magnetic resonance (NMR) investigations of both interacting partners should be established. In this thesis the stability of PsbQ in different buffers, as well as the influence of pH, temperature and salt concentration was investigated. Following stability tests, candidate buffer conditions were chosen for further NMR experiments exploring the influence on protein conformation and dynamics. Previously it had been found that Bis-Tris buffer provides suitable conditions for PsbP, while PsbQ had been investigated in phosphate buffer. In this work I established, that Bis- Tris buffer is appropriate for PsbQ as well, but that it may undergo structural and dynamical changes as evidenced by NMR experiments on recombinant stable isotope (N-15) labeled protein preparations. Some newly observed nuclear Overhauser effect (NOE) correlation indicate possible interactions from the N-terminal stretch to a loop region between the four stable helices of PsbQ. This indicates a less flexible solution structure than the one found in phosphate buffer, which still deviates significantly from the earlier crystal structure. Further studies are required to refine a three-dimensional structure based on these NOEs and some characteristic chemical shift changes.
Conformational changes of PsbQ protein from PSII studied by NMR